Odpowiedź:
[tex]a)\ \ \sqrt{5-2\frac{3}{4}}*2=\sqrt{4\frac{4}{4}-2\frac{3}{4}}*2=\sqrt{2\frac{1}{4}}*2=\sqrt{\frac{9}{4}}*2=\frac{3}{\not2}*\not2=3\\\\\\b)\ \ \sqrt{5-2\frac{2}{9}}*3=\sqrt{4\frac{9}{9}-2\frac{2}{9}}*3=\sqrt{2\frac{7}{9}}*3=\sqrt{\frac{25}{9}}*3=\frac{5}{\not3}*\not3=5\\\\\\c)\ \ \sqrt[3]{5^2+2}=\sqrt[3]{25+2}=\sqrt[3]{27}=3\\\\\\d)\ \ \sqrt{5^2-2^2}=\sqrt{25-4}=\sqrt{21}\\\\\\e)\ \ \sqrt[3]{\frac{5^2}{2}*4-23}=\sqrt[3]{\frac{25}{\not2_{1}}*\not4^2-23}=\sqrt[3]{50-23}=\sqrt[3]{27}=3[/tex]
Wyrażenia,których wartość jest równa 3 to a) , c) , e)